Hubungan Dukungan Sosial Guru dan Efikasi Diri Siswa Dengan Motivasi Berprestasi Siswa Kelas 5 SDN Gugus V Mataram - Baiq Ayunda Mardianti; Darmiany Darmiany; Heri Setiawan (Journal of Science Instruction and Technology, 2021)
This study aims to determine the relationship between teacher social support and student self-efficacy with the achievement motivation of 5th graders at SDN Gugus V Mataram. This research approach is quantitative correlation research. The sample in this study were 5th-grade students of SDN Gugus V Mataram, totaling 147 students with proportional random sampling technique. The method used for data collection is in the form of a questionnaire. The data obtained were then processed by using product-moment correlation analysis techniques and multiple correlation analysis. The results showed that there was a positive and significant relationship between teacher social support and student self-efficacy together with student achievement motivation. With an R-value of 776 and a p of 0.000 which is smaller than 0.05. This shows that the higher the teacher's social support and student self-efficacy, the higher the student's achievement motivation. The level of the relationship can be seen from the coefficient of determination of 59.1%.